PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, KUALITAS AUDIT, DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2013-2015) - Naila Hidayah, 13.05.52.0208; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2017)
This study aimed to analyze the influence of corporate governance, company size, quality audits, and leverage on the integrity of financial statements of companies listed on the Stock Exchange. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2013-2015. The sample in this study using purposive sampling with a sample of 175. The method of analysis of this study uses linear regression analysis berganda. Hasil this study indicate that managerial ownership, institutional ownership, and the size of the company and significant positive effect on the integrity of financial statements, while the audit committee, the commissioner independent, audit quality, and leverage do not affect the integrity of financial statements.Keywords: Corporate Governance, Audit Committee, Independent Board, Managerial Ownership, Institutional Ownership, and Firm Size, Quality Audits, and Leverage, The Integrity of The Financial Statements